Modelos de gestión de la calidad en instituciones públicas de salud en México (Models of quality management in health public institutions in Mexico) - Narvaez, Claudia; Rivas, Luis Arturo; Chavez, Adela (Facultad de Contaduría Pública y Administración, 2015)
Abstract: This document describes the models of quality management in mexican public institutions in the medical field. And it is divided into three parts. In the first the most important work in the field, in the second part of the context in which the health system operates in Mexico, in the third part the quality model and their analysis is described graphically described. In the fourth part a discussion on models of health institutions in Mexico highlighting a proposal that rescues the model NARICHA relevant variables that must be a model of quality in a public health institution is done.